Social system of enterprise management as an opportunity to achieve social effects and sustainable development goals - Bukharina, Liudmyla; Pavliuk, Tetiana (Management and Entrepreneurship: Trends of Development, 2021)
The aim of the article is to explore the social management system in order to achieve positive effects and ensure the goals of sustainable development. The article examines in detail the system and process of managing the social work of enterprises at all hierarchical levels. The main functions of management concerning management of social system are defined. The main measures of the social management system are additionally defined. An analogy is made between the system of social management of the enterprise and the system of management of the social enterprise. The requirements for the choice of social management system are indicated. The importance of using innovations to promote the development of the enterprise and achieve social impact and protection of employees of the organization is emphasized. In the course of the research such general scientific methods were used as: theoretical, empirical, methods of analysis and generalization. Methods of generalization, comparison and analytical grouping of data were also actively used. Most successfully, systematic and comparative methods have also been used in the study. Due to the use of institutional and structural-functional approaches, the study was able to further practical application. The results of the study explain the need to use a systematic approach to the establishment of the entire social management system, in order to achieve the greatest social effect and further development of the enterprise by attracting and meeting the goals of sustainable development. JEL Classification: A13, M14, M19, M20.